Electrohydrodynamic jet printing of PZT thick film micro-scale structures - Wang, Dazhi; Zhu, Xiaohu; Liang, Junsheng; Ren, Tongqun; Zha, Wen; Dong, Weijie; Rocks, Sophie A.; Dorey, Robert A.; Xu, Zheng; Wang, Xing (Elsevier, 2015)
This paper reports the use of a printing technique, called electrohydrodynamic jet printing, for producing PZT thick film micro-scale structures without additional material removing processes. The PZT powder was ball-milled and the effect of milling time on the particle size was examined. This ball-milling process can significantly reduce the PZT particle size and help to prepare stable composite slurry suitable for the E-Jet printing. The PZT micro-scale structures with different features were produced. The PZT lines with different widths and separations were fabricated through the control of the E-Jet printing parameters. The widths of the PZT lines were varied from 80 μm to 200 μm and the separations were changed from 5 μm to 200 μm. In addition, PZT walled structures were obtained by multi-layer E-Jet printing. The E-Jet printed PZT thick films exhibited a relative permittivity (ɛr) of ∼233 and a piezoelectric constant (d33, f) of ∼66 pC N−1.
Keywords: Electrohydrodynamic jet; Printing; PZT; Thick film